"New White Ethnics" or "New Latinos"? Hispanic/Latino Pan-ethnicity and Ancestry Reporting among South American Immigrants to the United States. Issue 4 (December 2021) - Schut, Rebecca A.
This article explores the identification patterns of South American immigrants to the United States, as measured via Hispanic/Latino ethnicity and ancestry reporting on the US Census. Using data from the 2006–2010 and 2011–2015 American Community Survey, my analysis reveals four main findings. First, I show significant heterogeneity in identity patterns and in sociodemographic, immigration, and geographic characteristics between South American and Mexican immigrants in the United States. Second, I find that Southern Cone immigrants opt not to report Hispanic/Latino ethnicity and "birth-country" ancestry (ancestry that is concordant with birth country, such as Colombian or Chilean) to a greater extent than Andean immigrants and, instead, report more distal "ancestral-origin" ancestries (i.e., Spanish, Japanese, etc.). Third, I show that those immigrants who do report Hispanic/Latino ethnicity are more likely to report "birth-country" ancestry than "ancestral-origin" ancestry, net of other factors. Finally, my analysis demonstrates that Brazilian immigrants chart a different path of identification among South American immigrants and almost unanimously do not report Hispanic/Latino ethnicity while overwhelmingly reporting "Brazilian" ancestry. Taken together, variation in Hispanic/Latino ethnicity and ancestry reporting across South American immigrant groups has implications for their incorporation into US society, as well as for the degree to which these immigrants see themselves as racialized actors in the United States. Some South American immigrant groups (Southern Cone immigrants) appear to be incorporating as "New White ethnics, " and others (Andean immigrants) appear to be incorporating as "New Latinos." Researchers of international migration should carefully consider these identification differences and their implications for the measurement and study of "Hispanic/Latino" immigrants and their descendants in the United States.